Exploring the Synthesis, Band Edge Insights, and Photoelectrochemical Water Splitting Properties of Lead Vanadates - Kalanur, Shankara S.; Lee, Young Jae; Seo, Hyungtak (ACS Applied Materials and Interfaces, 2021)
Exploring the ideal and stable semiconductor material for the efficient photoelectrochemical (PEC) overall water splitting reaction has remained a major challenge. Herein, we develop a facile hydrothermal method for the fabrication of monoclinic Pb3[VO4]2 and orthorhombic PbV2O6 thin films for the efficient and stable PEC overall water splitting applications. Detailed characterization was performed to study the crystal structure and optical, electrical, and electrochemical properties. The band edge positions of Pb3[VO4]2 and PbV2O6 are determined using spectroscopic data, revealing the conduction band edge positioned near the water reduction potential [∼0 V vs reversible hydrogen electrode (RHE)] and the valence band edge positioned well above the water oxidation potential, indicating the possible utilization of photogenerated electrons and holes for efficient water reduction and oxidation, respectively. With the optimized PbV2O6 thin films, a maximum photocurrent of 0.35 mA cm-2 was obtained at 1.23 V versus RHE and the stable production of both O2 and H2 is observed with >90% Faradaic efficiency. Importantly, this work demonstrates the possibility of utilizing lead vanadate materials for PEC water splitting applications.
Keywords: Conduction band edge; Faradaic efficiencies; Hydrothermal methods; Photoelectrochemical water splitting; Photoelectrochemicals; Photogenerated electrons; Reversible hydrogen electrodes; Water splitting reactions; band edge; crystal structure; Pb3[VO4]2; PbV2O6; photoelectrochemical water splitting